COMPARATIVE STUDY THE EFFECT OF INQUIRY AND CONVENTIONAL LEARNING METHODS ON LEARNING OUTCOMES OF CLASS VII STUDENTS' INDONESIAN SPEAKING SKILLS - wahuni, dwi (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2022)
This study aims to determine the effect of the inquiry learning method and conventional learning methods on student learning outcomes. This learning method refers to general statements, special statements, and making conclusions. The subjects of this study were 60 students who were divided into 2 (two) class VII students of SMP Prajamukti Kosgoro Purwoharjo using the population recearch method. This research was conducted at the researcher's workplace so that it used a purposive sampling method. The data collection technique was done by giving questionnaires and tests. Analysis of the data used to test the hypothesis using multiple linear regression on hypotheses 1 and 2, while for hypothesis 3 using the t-test. The results of the hypothesis test state that there is an effect of the use of the inquiry and conventional learning methods on the learning outcomes of the VII grade students, where the learning outcomes of students taught using the inquiry learning method have better test results than students taught using conventional learning methods. It is recommended for educators who use the inquiry learning method to really prepare technical matters, before carrying out learning, students are given explanations, prior training or mentoring, guidance for group work activities